2009
DOI: 10.4161/cc.8.17.9410
|View full text |Cite
|
Sign up to set email alerts
|

WRN helicase promotes repair of DNA double-strand breaks caused by aberrant mismatch repair of chromium-DNA adducts

Abstract: Recent studies in yeast have found that processing of DNA-double strand breaks (DSB) for recombination repair involves Sgs1 helicase. Human cells have five Sgs1 homologues with unknown selectivity and significance for repair of different DSB types. Here we examined the importance of WRN helicase in repair of G2-specific DSB caused by abnormal mismatch repair (MMR) of ternary Cr-DNA adducts. We found that Cr(VI) induced a rapid dispersal of WRN from the nucleolus resulting in its prolonged retention in the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 58 publications
(109 reference statements)
3
34
0
Order By: Relevance
“…WRN interacts with several proteins involved in the repair of DNA DSB and localizes to the sites of laser-induced DSB in live cells [100]. A recent study reported a higher persistence of gH2AX/53BP1 foci in human WRN-deficient fibroblasts compared with controls for up to 24 h after being treated with 20 mM of the potent human carcinogen, chromium Cr(VI), indicating impaired DSB repair due to abnormal mismatched repair [101]. This result suggests that the WRN protein may play an important role in repairing a specific class of DSB in human cells.…”
Section: Fibroblastsmentioning
confidence: 97%
“…WRN interacts with several proteins involved in the repair of DNA DSB and localizes to the sites of laser-induced DSB in live cells [100]. A recent study reported a higher persistence of gH2AX/53BP1 foci in human WRN-deficient fibroblasts compared with controls for up to 24 h after being treated with 20 mM of the potent human carcinogen, chromium Cr(VI), indicating impaired DSB repair due to abnormal mismatched repair [101]. This result suggests that the WRN protein may play an important role in repairing a specific class of DSB in human cells.…”
Section: Fibroblastsmentioning
confidence: 97%
“…The unique unidirectional uptake of tetrahedral chromate through nonselective ion channels has been shown to result in high levels of chromate in exposed cells (3) and a variety of gross morphological changes in DNA structure. While many types of DNA lesions have been postulated to occur from chromate exposure, including DNA adducts (4), DNA-protein crosslinks (5), double-strand breaks (6), and oxidation of DNA bases (7), little structural data on the nature of these lesions, their mutagenic effects and their cellular prevalence have been forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…3840 Mechanistically, DSBs arise from recognition and processing of Cr-DNA adducts by mismatch repair in replicated DNA. 38,39,41 Thus, formation of DSBs can serve as an important test for the assessment of genotoxic activity of Cr(VI) compounds and intracellular delivery of chromate anions either directly or as a result of particle dissolution inside the cell.…”
Section: Resultsmentioning
confidence: 99%